THE RELATIONSHIP BETWEEN OXYGEN SATURATION AND EPITHELIALIZATION IN GANGRENE PATIENTS IN THE JEMBER AREA - Zahro, Novita; Eka Pranata, Andi; Cahyono, Hendra Dwi (LPPM Universitas dr. Soebandi, 2025)
Diabetic ulcers or gangrene is a complication of diabetes mellitus resulting from angiopathy neuropathy and vascular disorders in the foot area. Gangrene wounds are caused by vascular disorders, nerves, and infection. If gangrene wounds are not handled properly and quickly, the wound will get worse. This study aimed to analyze the relationship between oxygen saturation and epithelialization in gangrene patients in the Jember area. Correlation analytical research design with a cross-sectional approach. The population of patients with gangrenous wounds consisted of 30 respondents using a quota sampling technique. The measuring tool uses oximetry and the Bates Janson Wound Assessment Tool checklist for Chi-Square (Fisher Exact) test analysis. Most of the gangrenous patients (63.3%) had normal oxygen saturation values ​​and almost all (80.0%) of patients had epithelialized gangrene >50%. KK = 0.436 means the relationship is sufficient. The conclusion is that there is a sufficient relationship. between oxygen saturation and epithelialization in gangrene patients in the Jember area. It is suggested that this research can be developed more completely and perfectly regarding GDA examination and participating in debridement during wound care.